INTEREST LEVEL OF ELEMENTARY SCHOOL STUDENTS IN LEARNING MUSIC CONTAINING CHILDREN'S SONGS - Sri Kartika Dewi; Resa Respati; Rosarina Giyartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze elementary school students' interest in learning music through children's songs. Interest is examined through three main aspects, namely student involvement, enjoyment, and interest. This study employs a descriptive quantitative approach using simple random sampling techniques. The sample consists of 361 elementary school students from Phase A, Phase B, and Phase C in Sariwangi Subdistrict. The data collection instrument is a closed-ended questionnaire with 15 statements on a four-point Likert scale. The data were analyzed descriptively using statistical software. The results showed that student engagement was in the moderate category with a percentage of 59.8%, while student enjoyment was also in the moderate category with a percentage of 67.03%. Conversely, interest showed a very high result of 98.09%. These findings indicate that, overall, students' interest in music education is quite high, but their engagement and feelings of enjoyment are not yet optimal. This suggests that while the song-based learning approach is effective in capturing attention, learning strategies need to be further developed to enhance active participation and emotional satisfaction during the learning process. Therefore, teachers are encouraged to design more interactive and enjoyable methods to support comprehensive engagement in music education.